Effects of Oral Drugs on Coronary Microvascular Function in Patients Without Significant Stenosis of Epicardial Coronary Arteries: A Systematic Review and Meta-Analysis of Coronary Flow Reserve - Yong, Jingwen; Tian, Jinfan; Yang, Xueyao; Xing, Haoran; He, Yi; Song, Xiantao (Frontiers in Cardiovascular Medicine, 2020)
Abstract Objective This study aims to investigate the impact of cardiovascular medications on the coronary flow reserve (CFR) in patients without obstructive coronary artery disease (CAD). Methods We searched PubMed, EMBASE, and Cochrane databases from inception to 15 November 2019. Studies were included if they reported CFR from baseline to follow-up after oral drug therapy of patients without obstructive CAD. Data were pooled using random-effects modeling. The primary outcome was change in CFR from baseline to follow-up after oral drug therapy. Results A total of 46 studies including 845 subjects were included in this study. Relative to baseline, the CFR was improved by angiotensin converting enzyme (ACEIs), aldosterone receptor antagonists (ARBs) (SMD: 1.12; 95%CI: 0.77 to 1.47), and statins treatments (SMD: 0.61; 95%CI: 0.36 to 0.85). 6-12 months of calcium channel blockers (CCBs) treatments improved CFR (SMD: 1.04; 95%CI: 0.51 to 1.58). Beta-blocker (SMD: 0.24; 95%CI: -0.39 to 0.88) and ranolazine treatment (SMD: 0.31; 95%CI: -0.39 to 1.01) was not associated with improved CFR. Conclusions Therapy with ACEIs, ARBs, and statins was associated with improved CFR in patients with confirmed or suspicious CMD. CCBs also improved CFR among patients followed for 6 to 12 months. Beta-blocker and ranolazine had no impact on CFR. Keywords: Oral drug, coronary microvascular, microvascular function, coronary flow reserve